PENGARUH STRUKTUR MODAL DAN RASIO AKTIVITAS TERHADAP PROFITABILITAS DENGAN LIKUIDITAS SEBAGAI VARIABEL MODERATING - Sunaryo, Deni; Adiyanto, Yoga; Indri, Dessy Dwi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
This study aims to continue previous research by adding different variables and knowing the differences in the results of the effect ofcapital structure and activity ratio on profitability with liquidity as a moderating variable. This research is a quantitative research using secondary data. The research object used is the chemical sub-sector companies on the Southeast Asian Stock Exchange in 2012-2020. The sampling method used is purposive sampling, in order to obtain 19 companies that present complete financial statements and annual reports and obtain 171 sample data. The data analysis techniques used were descriptive statistics, classical assumption tests, classical assumption tests, multiple regression analysis, hypothesis testing, namely partial and simultaneous tests and moderated regression analysis (MRA) which were processed using the SPSS 23 application. Based on the results of this study, it is known that the results of the t test for capital structure as proxied by long term debt to equity ratio have no effect on profitability as proxied by return on equity but the activity ratio proxied by total assets turnover has a positive and significant effect on profitability. The results of the F test show that the capital structure and activity ratio have a joint effect on profitability. for the results of the moderation regression test of model 1, it is known that the liquidity proxied by the current ratio is able to moderate but weaken the relationship between capital structure and profitability, but the results of the regression test of model 2 show that liquidity is able to moderate and strengthen the relationship between the ratio of activity to profitability